In vitro susceptibility profile of Plasmodium falciparum clinical isolates from Ghana to antimalarial drugs and polymorphisms in resistance markers - Zhao, Wei; Li, Xinxin; Yang, Qi; Zhou, Longcan; Duan, Mengxi; Pan, Maohua; Qin, Yucheng; Li, Xiaosong; Wang, Xun; Zeng, Weilin; Zhao, Hui; Sun, Kemin; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Drug resistance in Plasmodium falciparum compromises the effectiveness of antimalarial therapy. This study aimed to evaluate the extent of drug resistance in parasites obtained from international travelers returning from Ghana to guide the management of malaria cases. Eighty-two clinical parasite isolates were obtained from patients returning from Ghana in 2016–2018, of which 29 were adapted to continuous in vitro culture. Their geometric mean IC50 values to a panel of 11 antimalarial drugs, assessed using the standard SYBR Green-I drug sensitivity assay, were 2.1, 3.8, 1.0, 2.7, 17.2, 4.6, 8.3, 8.3, 19.6, 55.1, and 11,555 nM for artemether, artesunate, dihydroartemisinin, lumefantrine, mefloquine, piperaquine, naphthoquine, pyronaridine, chloroquine, quinine, and pyrimethamine, respectively. Except for chloroquine and pyrimethamine, the IC50 values for other tested drugs were below the resistance threshold. The mean ring-stage survival assay value was 0.8%, with four isolates exceeding 1%. The mean piperaquine survival assay value was 2.1%, all below 10%. Mutations associated with chloroquine resistance (pfcrt K76T and pfmdr1 N86Y) were scarce, consistent with the discontinuation of chloroquine a decade ago. Instead, the pfmdr1 86N-184F-1246D haplotype was predominant, suggesting selection by the extensive use of artemether-lumefantrine. No mutations in the pfk13 propeller domain were detected. The pfdhfr/pfdhps quadruple mutant IRNGK associated with resistance to sulfadoxine-pyrimethamine reached an 82% prevalence. In addition, five isolates had pfgch1 gene amplification but, intriguingly, increased susceptibilities to pyrimethamine. This study showed that parasites originating from Ghana were susceptible to artemisinins and the partner drugs of artemisinin-based combination therapies. Genotyping drug resistance genes identified the signature of selection by artemether-lumefantrine. Parasites showed substantial levels of resistance to the antifolate drugs. Continuous resistance surveillance is necessary to guide timely changes in drug policy.